Gas liquid separation within a novel axial flow cyclone separator - Dickson, Philip James (Cranfield University, 1998)
Cyclone separators have been described in detail and, although substantial research has been performed on solid / gas devices, the use of cyclones for gas / liquid separation has been comparatively ignored; this is particularly true for higher concentrations of liquid and for degassing applications. Consequently no generic models are available which will predict separation efficiency or pressure drop for all designs of cyclone. A novel design of axial flow cyclone called WELLSEP was examined for the purpose of degassing. This design was not believed to be optimal and no design criteria or performance prediction models were available for it. An experimental programme was therefore produced and executed to investigate changes in geometry and the affect of fluid dynamics. Changes to the length, vortex finder and swirl generator were examined first and then one design was selected and tested over a number of liquid flow rates, Gas Void Fractions (GVFs) and liquid extractions. Data was collected from the experiments which assisted in the development of semi-empirical models for the prediction of pressure drop and separation efficiency. These models could be used in the design of WELLSEP. Geometric and fluid dynamics changes have both been shown to influence the performance of the tested cyclone. The principal conclusions that have been drawn from this research are: " Of the tested designs, the design based upon a 30mm vortex finder diameter, settling chamber length of three times the diameter of the cyclone and a four start helix gave the optimum separation efficiency over the greatest range of conditions. 0 The separation efficiency is affected by the superficial liquid velocity and the liquid extraction but not the GVF. " The dimensionless pressure drop coefficient (Euler number) is a function of liquid extraction and GVF. It may also be a function of the superficial liquid velocity but it is unproven by this research.